PENGARUH IKLAN, LABEL INFORMASI PRODUK, DAN NUTRITION KNOWLEDGE TERHADAP MINAT BELI SUSU SGM 3+ Di kota Pontianak - B1021161113, Rina Sinthawati (Jurnal Manajemen Update, 2020)
ABSTRAKThis study aims to examine and analyze the effect of advertising, product information labels, and nutrition knowledge toward purchase intention of SGM 3+ milk in Pontianak City. In this study, the population is mothers with a minimum age of 17 years, having children with an age range of 3 to 5 years, the respondents have seen an advertisement for SGM 3+ milk. The research was conducted in the city of Pontianak. The sample in this study amounted to 100 respondents, with purposive sampling technique and data analysis model using Multiple Linear Regression analysis. Based on the results of the t test research shows that advertising, Product Information Labels, and Nutrition Knowledge have a significant effect on purchase intention.DAFTAR PUSTAKADAFTAR PUSTAKAAbdurrahman, N.H.(2015). Manajemen Strategi Pemasaran, Bandung: CV. Pustaka Setia.Al-Aali. A., Randheer. K., Hasin. S., (2015).Do the subcomponents of country of originÂ Â triggerpurchase intentions? A Conceptual Model of Consumer Perceptions.Â Â Â Â Â Â Â International Journal of Commerce and Management, Vol. 25 No. 4 pp. 627- 640.Annunziata, A. and Vecchio, R. (2011).Functional foods development in the European market: a consumer perspective. Journal of Functional Foods, Vol. 3 No. 3, pp. 223-228.Ares, G., GimÃ©nez, A. and GÃ¡mbaro, A. (2008). Influence of nutritional knowledge on perceived healthiness and willingness to try functional foods.Â Appetite, Vol. 51 No. 3, pp. 663-668.Assael,Henry. (2001). Consumer Behaviour 6th Edition. Yew York: Thompson Learning.Augusty, Ferdinand. (2013). Metode Penelitian Manajemen. Semarang. Badan Penerbit Universitas Diponegoro.Balasubramanian, S.K. and Cole, C. (2002).Consumersâ€™ search and use of Nutrition information: the challenge and promise of the Nutrition Labeling and education act,.Journal of Marketing Vol. 66 No. 3, pp. 112-127.BreÄiÄ‡, R., Gorton, M. and Barjolle, D. (2014). Understanding variations in the consumption of functional foods â€“ evidence from Croatia. British FoodJournal. Vol.116No.4,pp.662-675.Childs, N.M. (1998).Public policy approaches to establishing health claims for food labels: an international comparison. British Food Journal. Vol. 100 No. 4, pp. 191-200.Detail Produk SGM 3 plus. Diakses dari https://www.generasimaju.co.id/detail-produk/sgm-eksplor-3-plusÂ Dharni. K. G. K. (2016). Use and influence of nutrition labeling: an emerging market experience. Nutrition & Food Science , Vol. 46 Iss 3 pp.Dianoux. C., Herrmann. E., Zeitoun. H. (2013).Comparative Advertising: Citing or not the Leading Brand and its Price.Journal of Consumer Marketing, Vol. 30 Iss 4 pp. 345 â€“ 354.Disduk Capil Pontianak.(2019).Jumlah Penduduk Kota Pontianak Semester I-Tahun 2019. Diakses dari https://disdukcapil.pontianakkota.go.id/jumlah-penduduk-kota-pontianak-semester-i-tahun-2019-berjumlah-667053-jiwaEngel dkk.(2002). Perilaku konsumen.Alih bahasa Drs. F.X. Budiyanto. Jakarta: Binarupa Aksara.Ghozali.(2005). Aplikasi Analisis Multivarativariate dengan program SPSS.Semarang : Badan Penerbit Universitas Diponegoro.Hussin, S.R., Hashim, H., Yusof, R.N. and Alias, N.N. (2013).Relationship between product factors, advertising, and purchase intention of halal cosmetic.Pertanika Journal of Social Sciences & Humanities, Vol. 21 No. S85, pp. 85-100.Hoque. M. Z., Xie. J., Nazneen. S., (2018).Effect of Labelled Information and Sensory Attributes on Consumersâ€™ Intention to Purchase Milk.South Asian Journal of Business Studies Vol. 7 No. 3 pp. 265-286.Jumlah Penduduk wilayah kota Pontianak 2019. Diakses dari https://disdukcapil.pontianakkota.go.id/jumlah-penduduk-kota-pontianak-semester-i-tahun-2019-berjumlah-667053-jiwaLalor.F., Kennedy. J., Wall.G.P., (2011). Impact of Nutrition Knowledge on Behaviour Towards Health Claims on Foodstuffs. British Food Journal, Vol. 113 Iss 6 pp. 753 â€“ 765.Jefkins, Frank. (2009). Periklanan.Jakarta: Erlangga.Julita Nainggolan RZ. (2011). Hubungan antara Pengetahuan dan Sikap Gizi Ibu dengan Status Gizi Balita di Wilayah Kerja Puskesmas Rajabasa Indah Kedokteran.pp.62-72.Keller, Kevin L. (1998). Strategic Brands Management: Buildings, Measuring, and Managing Brand Equity, New Jersey: Prentice Hall, Inc.Khuong, N.M. and Nguyen, D.T. (2015).The effects of television commercials on customers purchase intention â€“ a study of milk industry in Ho Chi Minh City, Vietnam. Â Journal of Economics, Business and Management, Vol. 3 No. 9, pp. 851-857.Kotler dan Amstrong.(2008). Prinsip-prinsip Pemasaran.Jilid 1 dan 2.Edisi 12. Jakarta: Erlangga.Kotler.P dan Keller. L. K. (2008). Manajemen Pemasaran. Jilid 2 edisi 13.Jakarta : Erlangga.Kozup, J.C., Creyer, E.H. and Burton, S. (2003). Making healthful food choices: the influence of health claims and nutrition information on consumersâ€™ evaluations of packaged food products and restaurant menu items.Journal of Marketing, Vol. 67 No. 2, pp. 19-34.KreÅ¡iÄ‡. G.,Â LioviÄ‡. N. (2019). Effects of menu labeling on studentsâ€² food choice: a preliminary study. British Food Journal Vol. 121 No. 2.Lisa M. Soederberg Miller, Diana L. Cassady. (2015). The effects of nutrition knowledge on food label use. A review of the literature. Appetite 92 (2015) 207â€“216.Lu.J. (2015).The effect of perceivedcarrier-ingredient fit on purchaseintention of functional food moderated by nutritionknowledge and health claim. British Food Journal, Vol. 117 Iss 7 pp. 1872 -1885.Miller, L.M.S. and Cassady, D.L. (2015).The effects of nutrition knowledge on food label use: a review of the literature, Appetite.Journal Vol. 92, pp. 207-216.Morris, J. (1997). Green goods Consumers, product labels and the environment, The Environment Unit, London.Morissan. (2010). Periklanan : Komunikasi Terpadu Edisi Pertama.Jakarta : Prenamedia Group.Peraturan badan pengawasan obat dan makanan nomor 31 tahun 2018 tentang label pangan olahan.Puspitalena. A., Palupi. S. N., Giriwono. E. P. (2015). Peran Klaim Kesehatan pada Susu Pertumbuhan sebagai Penentu Keputusan Pembelian.Jurnal mutu pangan, vol. 2(2)Â : 144 â€“ 151, 2015.Putra.A. (2017).Pengaruh Iklan dan Kepercayaan Merek Terhadap Minat Beli Konsumen Texsas Pekanbaru.JOM FISIP Vol.4 No. 1.Roe, B., Levy, A.S. and Derby, B.M. (1999) The impact of health claims on consumer search and product evaluation outcomes: results from FDA experimental data. ,Journal of Public Policy & Marketing, Vol. 18 No. 1, pp. 89-105.Rospond, R. M. 2008. Penilaian Status Nutrisi. http://www.lyrawati.files.wordpress.com/2008/07/penilaian-status nutrisi.pdf.Sanusi.A. (2015).Manajemen Strategi Pemasaran. Bandung :Pustaka Setia.Saputra.R. (2018).Pengaruh Iklan dan Citra Merek Terhadap Minat Beli Konsumen Produk Merek Honda.JOM FISIP, Vol. 5 No. 1.Saraswati. G. G. L., Suamba. I. K., Parining. N. (2015).Faktor-faktor yang Berperan dalam Keputusan Konsumen Mengkonsumsi Produk Susu Bubuk Dancow Instant Enriched di Kota Denpasar.E-Jurnal Agribisnis dan Agrowisata, Vol.4, No.4.Santoso.S. (2004).Mengatasi Berbagai Masalah Statistik dengan SPSS versi 11.5. Jakarta: Gramedia.Schiffman dan Kanuk.(2007) .Perilaku Konsumen Edisi Kedua.Jakarta: PT. Indeks Gramedia.Siregar.S. (2013).Metode Penelitian kuantitatif: dilengkapi dengan perbandingan perhitungan manual spss. Jakarta: KencanaSparke, K. and Menrad, K. (2009).Cross-European and functional food-related consumer segmentation for new product development. Journal of Food Products Marketing, Vol. 15 No. 3, pp. 213-230.Stanton, Wiliam J. (2010). Prinsip Pemasaran Edisi Ketujuh Jilid 1. Jakarta: Penerbit Erlangga.Sundalangi.M., Mandey. L.S., Jorie. J. R., (2014). Kualitas Produk, Daya Tarik Iklan, dan Potongan Harga Terhadap Minat Beli Konsumen Pizza Hut Manado.Jurnal EMBA Vol.2 No.1.Sugiyono, (2014).Statistika untuk Penelitian.Â Bandung: Alfabeta.Supariasa, dkk.2002. Penilaian Status Gizi.Jakarta : Penerbit Buku Kedokteran EGC.Top Brand Award.(2018). Situs Web Top Brand Award. Diakses dari https://www.topbrand-award.com/en/2018/05/susu-formula-kids-2018/Top Brand Award.(2018). Situs Web Top Brand Award. Diakses dari https://www.topbrand-award.com/en/2019/05/susu-formula/Urala, N. and LÃ¤hteenmÃ¤ki, L. (2004).Attitudes behind consumersâ€™ willingness to use functional foods. Food Quality and Preference Vol. 15 Nos 7-8, pp. 793-803.Urala, N., Schutz, H. and Spinks, J. (2011).Consumer perceptions of â€˜Functional Foodâ€™ in the United States. Journal of Food Products Marketing, Vol. 17 No. 4, pp. 407-419.Yoon. J. H., George. T., (2012).Nutritional information disclosure on the menu: Focusing on the roles of menu context, nutritional knowledge and motivation.International Journal of Hospitality Management 31 (2012) 1187â€“ 1194.Yusuf.M, (2014).Metode Penelitian : Kuantitatif, Kualitatif & Penelitian Gabungan Edisi Pertama. Jakarta: Prenadamedia GroupWalpole, Ronald E (2001) â€œPengantar Statistikaâ€œ, edisi ke-3, Jakarta: PT. Gramedia.Williams, P. (2005), â€œConsumer understanding and use of health claims for foodsâ€, Nutrition Reviews, Vol. 63 No. 7, pp. 256-264.www.generasimaju.co.idwww.pontianakkota.go.idwww.topbrand-award.com